Utilization of 12 health packages extended under Ayushman Arogya Mandir in block Marh, Jammu, Jammu and Kashmir - Aashima Magotra; Harjeet Rai; Varalakshmi Chandra Sekaran; Sharpi Sharma (Elsevier, 2024)
Background: The establishment of the Ayushman Arogya Mandir marks a fundamental change in India's approach to healthcare. The present study aimed to examine the effectiveness and shortcomings of health packages extended through the Ayushman Arogya Mandir in Block Marh, Jammu, Jammu and Kashmir identifying areas for improvement, and addressing barriers to optimal utilization. Methods: This cross-sectional study was done among 10 centres in the Marh block of Jammu, Jammu and Kashmir to achieve the desired objectives using structured and self-administered questionnaires. A convenience sampling of 105 participants, including 55 healthcare professionals and 50 community members, was adopted using time-bound enumeration. Checklists were also included to assess healthcare services, ensuring a thorough understanding of how healthcare packages are administered and implemented. Confidentiality was prioritized and ethical considerations guided the data collection process, allowing for a comprehensive examination of healthcare utilization patterns in the target region. Results: The results revealed that reproductive and family planning services, as well as neonatal/infant healthcare, have high utilization rates (95 % and 78 %, respectively), highlighting their significance, whereas lower rates in elderly/palliative care, psychiatric/neurological/substance use disorder care, and eye/ENT treatments indicate potential areas for improvement in healthcare awareness, access, and service provision barriers. Conclusion: The Ayushman Arogya Mandir in Block Marh, Jammu, Jammu and Kashmir are heavily leaning towards maternal and child health initiatives while other services are underutilised, highlighting the need for targeted awareness of the availability and accessibility to these services.